Evaluation of the Impact of 2 Disposable Diapers in the "Natural" Diaper Category on Diapered Skin Condition. (June 2019) - O'Connor, Robert J.; Sanchez, Veronica; Wang, Y.; Gibb, Roger; Nofziger, Donald L.; Bailey, Mary; Carr, Andrew N.
The demand for natural infant care products, including diapers, has increased. However, few disposable diapers have been able to provide the performance caregivers desire while also incorporating ingredients consistent with the "natural" category. In an examiner-blinded clinical study, the performance of a new cotton-enhanced diaper with high-performance materials was compared with an existing natural diaper offering. A total of 131 infants wore 1 of the 2 diapers for a 4-week period. Diaper performance was assessed based on skin marking assessments, scored by a trained grader, and incidence of diaper dermatitis. Skin grading for diaper dermatitis was assessed at 4 sites in the diaper area. The new diaper offering was associated with less skin marking and significantly less diaper rash at the genitals and intertriginous regions versus the comparator. These data suggest that the new diaper provided significant improvement in both skin marking and prevalence of diaper rash.